Language Learning Strategies and Motivation As Determinants of the English Academic Performance of Grade 10 Students - Giangan, Mary Grace (Journal of Interdisciplinary Perspectives, 2024)
The academic performance in English is essential to students' overall learning outcomes. This study aimed to determine the relationship between language learning strategies, motivation, and English academic performance among Grade 10 students. A descriptive-correlational design was employed, and participants were selected through stratified random sampling from three schools in Tagum City. The mean was used to describe the students' level. The statistical tools used included the mean, standard deviation, and Pearson-r correlation coefficient. The study found that Grade 10 students exhibited a high level of language learning strategies, suggesting that these strategies helped students become more effective learners and fostered more efficient development of their mastery of the target language. Additionally, students demonstrated a high level of motivation, indicating frequent motivation in learning. The study also revealed a satisfactory level of English academic performance, suggesting that there are still areas needing improvement. Furthermore, the two independent variables were significantly correlated with the English academic performance of Grade 10 students.